Performance and Strategies to Develop Waste Business - Dika Anggari; Ujang Sumarwan; Lilik Noor Yuliati (School of Business, IPB University (SB-IPB), 2017)
The objectives of this study are to measure the performance conducted based on the generating of turnover and magnitude of volume of wastes deposited by the waste sellers to CV. MBG and to analyze alternative strategies on waste business, especially for CV. MBG, through four perspectives on the Balanced Scorecard method. In addition, this study also analyzed the priorities of the four perspectives using ANP. The results show that the turnover per day can reach 94 million rupiah, and the volume generated per day can reach 12 tons. Furthermore, there are four perspectives that can measure the performance and internal process perspective as a priority to be more noticed. The conclusion of the research result shows that waste business becomes one of the most promising businesses. The managerial implication of this study is that the four BSD perspectives sorted according to their priorities from the ANP can be applied to support the company performance.Keywords: performance measurement, waste processing, analytical network process, Balanced Scorecard, CV MBG